City Profile: Dar es Salaam, Tanzania. (September 2019) - Todd, Gemma; Msuya, Ibrahim; Levira, Francis; Moshi, Irene
Cities in Africa are experiencing fast urbanization with growing demand for basic services. The city of Dar es Salam, one of the fastest growing cities in the region and the world, is likely to guide the urban future in Tanzania. Dar es Salaam is the former capital city of Tanzania and retains its importance as most of the government offices were located. However, the whole process of complete relocation of government offices to the present capital city of Dodoma might affect the dynamics in Dar es Salaam in the near future. Nevertheless, it is the leading commercial centre and economic hub in Tanzania and is expected to be a mega city by 2030. The growth of the city is construed by both natural increase and high rate of migration. However, the city's organic growth was affected by racial-based residential segregation under the colonial regime, whose imprints are evident to date. In this profile, an overview of Dar es Salaam's colonial, post-colonial, social, economic and location factors that led to urbanization is provided. This profile highlights the previous, current and future challenges, and explores the pathways to enhance sustainability and transformation of Dar es Salaam to be a smart city. Poor implementation of master plans led to minimal guidance of city growth, but the current land and and human settlement policy emphasizes on sustainable approach in urban planning including low costs but sustainable settlements even for the urban poor. Such transformation requires government and city management to invest in better planning implementation, creation of database that will inform future planning, improvement in social services such as infrastructure, access to quality and affordable housing, water and electricity supply. This paper contributes to the existing literature on nature of cities in developing countries, which had been affected by colonialism and poor implementation of policies, and suggest ways in which cities can to become smarter and sustainable.